The signature in law : from the thirteenth century to the facsimile - Mason, Stephen (Barrister) (OBServing law, 2022)
Since the thirteenth century, the signature has been used to demonstrate proof of intent. This book puts the concept of the signature into a broad legal context, setting out the purposes and functions of a signature. Drawing on cases from common law jurisdictions across the world, this book demonstrates that judges expanded the meaning of the signature as technologies developed and were used in unanticipated ways. Following an overview of the historical methods used to demonstrate proof of intent and authentication, the book considers the judicial response to the variations in form that signatures have been subject to over the past two hundred years, from initials, partial signatures, and fingerprints to rubber stamps and typewriting. Past judicial decision-making not only demonstrates the flexibility of the form a signature can take but also confirms that judges had the flexibility of mind to accept the first forms of electronic signature (telex, facsimile transmission) without the aid of special legislation. In this way, the signature is a prime example of the inherent flexibility of the English common law.